2009
DOI: 10.1111/j.1742-4658.2009.07083.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Kinesin‐3 NcKin3 motor domain and implications for neck function

Abstract: Members of the Kinesin‐3 family are microtubule motors involved in the transport of membranous cargo. NcKin3 from the fungus Neurospora crassa is dimeric but inactivates one of its motor heads to generate nonprocessive motility. To determine how one of the heads is inactivated, we investigated truncated monomeric constructs. None of the constructs generated processive single‐molecule motility, and multimotor velocities depended linearly on the number of residues remaining in the neck. The kinetic analysis sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…Previous variable-temperature in vitro motility assays with kinesins (8)(9)(10) have been limited to a relatively narrow temperature window that roughly covers the survival range of most mammals. Broader ranges have been explored via biochemical methods (11,12), but not biophysical ones. Although published data on kinesin is somewhat limited, scant variable temperature data are available for cytoplasmic dynein.…”
Section: Introductionmentioning
confidence: 99%
“…Previous variable-temperature in vitro motility assays with kinesins (8)(9)(10) have been limited to a relatively narrow temperature window that roughly covers the survival range of most mammals. Broader ranges have been explored via biochemical methods (11,12), but not biophysical ones. Although published data on kinesin is somewhat limited, scant variable temperature data are available for cytoplasmic dynein.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, kinesin 3 from Neurospora crassa, NcKin3, was shown to be dimeric, but inactivates one of its motor heads to generate non-processive motility [17]. The data of Adio and Woehlke confirmed that the neck domain is required for dimerization and is essential for NcKin3 function: the absence of the neck altered the kinetic cycle fundamentally [18].…”
Section: Resultsmentioning
confidence: 98%
“…NcKin3 is a dimeric plusend-directed motor. The amino acid sequences of the heads are identical, but only one of the motor domains participates in hydrolyzing ATP and MT binding (7,44). The x-ray structure of the NcKin3 motor domain did not reveal any unusual features that could be linked to this unusual behavior of the motor domains (8).…”
Section: Discussionmentioning
confidence: 98%